Syntactic Word Order between Indonesian and English: Building a Concept through Contrastive Analysis in Academic Writing - Mochamad Imron Azami; Fitri Awaliyatush Sholihah (Universitas PGRI Madiun, 2021)
This study focuses more on syntactic word order through identify the language structure of simple sentence both Indonesian and English in argumentative essay made by English education department students at University of Islam Malang and analyze it by contrastive analysis (CA). The significance of this research is to cover the students’ difficulties in academic writing process by using contrastive analysis and to identify the highlight point of the structure differences between Bahasa Indonesia (L1) and English (L2). The researcher used qualitative method by collecting 10 students’ argumentative essay both in Indonesia and in English. The results show that the common pattern occurs in the students’ argumentative essay is SVO and the other patterns are S-V(Aux)-O, NP-S-V-O, Conj-S-V-O, S-V-O-V, S-S-V-O and Conj-NP-S-V-O. While in Indonesian are Subjek-Predikat (SV), Subjek-Predikat-Objek (SVO), Subjek-Predikat-Pelengkap (SVC), Subjek-Predikat-Objek-Pelengkap (SVOC), Subjek-Predikat-Objek-Keterangan (SVOA (Adverb)), Subjek-Predikat-Keterangan (SVA), Keterangan-Predikat-Subjek(AVS), and Subjek-Predikat-Keterangan-Pelengkap (SVAC). Students tended to write the argumentative essay in English inapropiately to the theory of simple sentence structure. While in Indonesian arguementative essay, they wrote properly based on the possible pattern of simple sentence in Indonesian.